Flow Characteristics Study of Wind Turbine Blade with Vortex Generators - Hao Hu; Xin-kai Li; Bo Gu (International Journal of Aerospace Engineering)
The blade root flow control is of particular importance to the aerodynamic characteristic of large wind turbines. The paper studies the feasibility of improving blade pneumatic power by applying vortex generators (VGs) to large variable propeller shaft horizontal axis wind turbines, with 2 MW variable propeller shaft horizontal axis wind turbine blades as research object. In the paper, three cases of VGs installation are designed; they are scattered in different chordwise position at the blade root, and then they are calculated, respectively, with CFD method. The results show that VGs installed in the separation line upstream, with the separation line of the blade root as a benchmark, show a better effect. Pneumatic power of blades increases by 0.6% by installing VGs. Although the effect on large wind turbines is not obvious, there is a space for optimization.